QUALITATIVE CHARACTERISTICS OF TECHNOLOGICAL PLATFORMS OF DISTANCE LEARNING - Kravtsov Г.М.; Odintsov, B.B. (Journal of Information Technologies in Education (ITE), 2010)
On the basis of requirements to Distance Learning Systems which are formulated according to standards IMS and SCORM, popular platforms of Distance Learning, including Open Source Software are analysed.